Implementasi Strategi Promosi Kesehatan dalam Upaya Pencegahan Penyakit Hipertensi di Puskesmas Katobengke - Rininta Andriani; Egryana Egryana; Dahmar Dahmar; Fitriani Fitriani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The number of hypertension sufferers in the Katobengke Community Health Center's work area has increased annually. In 2025, it ranked first among the 10 highest prevalence diseases, at 9.53% (1,116 cases), compared to 5.53% (479 cases) the previous year. The purpose of this study was to determine how health promotion strategies are implemented to prevent hypertension at the Katobengke Community Health Center. The research method was qualitative with a phenomenological approach. Nine informants were selected using purposive sampling. Data collection techniques included in-depth interviews, observation, and documentation. Data validity was validated using triangulation. The results showed that the implementation of health promotion strategies to prevent hypertension at the Katobengke Community Health Center has been implemented through advocacy, climate development, and community empowerment. In terms of advocacy, activities have been carried out through cross-sector coordination, but they have not been optimal due to a lack of continuity, resulting in inconsistent support and ongoing follow-up. In terms of climate building, it was found that outreach activities, integrated health posts (Posbindu), and the involvement of cadres and community leaders have been carried out consistently every month, fostering an environment conducive to healthy lifestyles. In terms of community empowerment, cadres have played an active role, but community participation in hypertension prevention programs remains lax, resulting in inconsistent behavior change. The conclusion of this study indicates that health promotion strategies for hypertension prevention at the Katobengke Community Health Center have been implemented through advocacy, climate building, and community empowerment. However, community attendance at routine hypertension prevention checkups remains inconsistent.